The Impact of PPG Program on the Performance of Pre-service and In-service English Teachers Based on School Principal Assessment. - Pandu Kesuma; Sitti Fatimah (Journal of English Language Teaching, 2021)
PPG (Pendidikan Profesi Guru) is an education program to prepare Bachelor graduates to be professional teachers in every subject they carry. PPG program is aimed to solve issues that emerge among teachers and improve their teaching competencies. This research is conducted to obtain information from School Principals in 50 Kota Regency and Payakumbuh City whose English teachers have graduated from the PPG Program at least two years ago (from 2019 backwards) regarding the impact of PPG program on teacher’s pedagogical and professional competencies. 21 in-service English teachers and two pre-service English teachers has been involved as the sample of this research. The type of this research is survey research with quantitative method. The data were collected by using close-ended and open-ended questionnaire distributed through Google-form. The findings of this research shows that PPG Program has brought positive impact towards English teachers’ performance according to school principals’ assessment. The majority of English teacher are considered worthy to sit on the positive scoring criterion. Although the numbers that falls under negative scoring criterion is arguably ignorable, English teachers still encounter minor issue that may or may not re-emerge throughout the years. The results and findings from this study are expected to improve the process of conducting PPG program so that later it will be able to produce a better quality of certified teachers. Furthermore, for the Ministry of Education and Culture as the one in charge of PPG program to improve and create a better education system in PPG program.